ANTIBACTERIAL ACTIVITY OF THE ESSENTIAL OILS Piper CrocatumRuiz & Pav. LEAVES - M, Soerya Dewi; Handayania, Nestri; Ngaisaha, Siti; Setyowati, Eliza Nur (Alchemy Jurnal Penelitian Kimia, 2013)
The aim of this research is to determine the chemical compounds and antibacterial activitiyof the essential oil of Piper crocatum Ruiz & Pav. leaves. GC-MS analysis shows that there are 16 components with Sabinene and?-mirceneas major component i.e 44.91% and 18.88 %, respectively.The Minimum Inhibition Concentration (MIC) for gram positive bacteries, i.e Bacillus cereus, Staphylococcus aureus andStaphylococcus epiderrmidis are1% ,0.25% and 0,5%, respectively. Meanwhile the MIC values for gram negative bacteries i.e Shigella flexneri, Eschericia coli andPseudomonas aeruginosa are 0.25 %, 1.0% and 0.75 %, respectively.